Scale of Subtle Prejudices Towards Disability at the University: Validation in Mexican Population - Andrés Sánchez-Prada; Carmen Delgado-Álvarez; Alicia Gurdián-Fernández (European Journal of Investigation in Health, Psychology and Education)
The purpose of this study was to analyze the adequacy of the “Subtle Prejudice Scale towards Disability in the University” for a university environment in Mexico. The theoretical model of this scale, which incorporates the gender dimension, was previously validated in Spain and Costa Rica with good psychometric properties and evidence of construct validity. The application of the scale in a Mexican university sample of 601 participants (83.4% students; 53.1% women and 45.3% men; aged 18 to 82, M = 25 years) confirmed the dimensional structure of the original four-factor model, with good fit indices through exploratory and confirmatory factor analysis and with adequate internal consistency for each dimension: avoidance of contact (ω = 0.81), benevolent idealization (ω = 0.77), excessive demands (ω = 0.73), and sexist amplification of prejudice (ω = 0.77). Relations between the scale dimensions and other variables (participants’ sex, political opinion, and preferred university policies for people with disabilities) were consistent with the current literature: men and right-wing people tend to show higher levels of ableism, which in turn are inversely associated with the supporting of inclusive policies. The results endorse the cultural validity of the scale and its suitability to evaluate ableism in Mexican universities.